KONSEP MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN LEMBAGA ISLAM DI MTs S SUNGAI RAMBAH KABUPATEN PADANG PARIAMAN - Aulia Gusli, Ramadhoni; M, Iswantir; Akhyar, Muaddyl (Jurnal Bilqolam Pendidikan Islam, 2023)
This study is motivated by the need for planning the procurement of facilities and infrastructure, because the madrasah has submitted proposals to receive assistance but not all of them have provided the expected results, resulting in a less than ideal learning environment due to inadequate facilities and infrastructure. There is still room for improvement in all aspects of facilities and infrastructure management, from initial inventory to final disposal. Therefore, there is room for development in the system used to oversee the operation of infrastructure and facilities. The purpose of the study was to identify and describe the factors that influence the development of infrastructure and services in the Sungai Rambah mountain range of Padang Pariaman Regency, including factors that encourage and hinder development. The analytical scriptural method was used to conduct this qualitative research. Interviews, field notes, and archival research were used to collect this data. Quantitative data analysis methods were not used to present information obtained from words, pictures, and actions. Applying for government assistance to plan facilities and infrastructure, purchasing facilities and infrastructure in accordance with the planning of facilities and infrastructure, using and maintaining facilities and infrastructure in accordance with the needs of students, conducting an annual inventory according to the provisions of the data, and abolishing goods in a timely manner depend on c. Based on these findings, schools are encouraged to prioritise the placement of student facilities to ensure the highest level of satisfaction among its customers. Keywords: Facilities and Infrastructure Management, Islamic Education Institution